Cochran v. City of Atlanta: Assessing the Relationship between Religious Liberty and Freedom of Speech - Joseph Prud’homme (Selected Topics in Humanities and Social Sciences Vol. 7, 2021)
This work assesses the relationship between religious liberty and freedom of speech in the United States constitutional context. Using the federal case of Cochran V. City of Atlanta as a Springbroad, the work argues that the recent trend of subsuming religious liberty under a broader freedom of expressive speech risks reducing the protections afforded the right of religious liberty.